Science and the media : Delgado's brave bulls and the ethics of scientific disclosure - Snyder, Peter J., 1964-; Mayes, Linda C.; Spencer, Dennis D.; ScienceDirect eBooks (Amsterdam ; Boston ; London : Academic, 2009)
Of great utility for every scientist faced with publicizing their discoveries via the media, this book addresses questions of responsibility for the balance and accuracy of scientific reporting, and attempts to be a guide for the scientist in their quest to inform the general public about their research in honest, truthful, and still interesting ways. Case studies by leading scholars in the fields of bioethics (pharmaceutical research (Declan Doogan, Senior VP Pfizer), medical journal editing (Jerome Kassirer, former editor of NEJM), science journalism, philosophy of science, history of medicine (John Warner, chair history of medicine Yale), public health (Ruth Katz, Dean public health, George Washington University), and philosophy of religion (Reverend Wesley Carr, former Dean of Westminster) illustrate positions and points of view and offer unique perspectives on the complex dance between science and the media. Provides a compelling overview and analysis of the difficulties of dealing with mass media and collects tips and solutions. Includes case studies from the experience of a number of high profile contributors from different fields. Provides an easy to read, carefully selected and synthesized overview well suited to teaching and as further reading source in respective classes. Includes a famous movie from Jose Delgado that shows his attempts in the 60s to demonstrate "remote control" of a bull.
Medicine, media, and the dramaturgy of biomedical research: historical perspectives / John H. Warner -- Delgado's brave bulls: the marketing of a seductive idea and a lesson for contemporary biomedical research / Peter J. Snyder -- Adrenal transplantation for Parkinson's disease / Dennis D. Spencer -- The use of SSRIs in the treatment of childhood depression: a scientific dialectic / Peter Fonagy -- Media coverage of stem cell research / David H. Smith, Aaron Klink, Julius Landwirth -- Medicine's obsession with disclosure of financial conflicts: fixing the wrong problem / Jerome P. Kassirer -- In support of industry-sponsored clinical research / Declan P. Doogan -- Prevailing truth: the interface between religion and science / Wesley Carr -- Science meets fundamentalist religion / Pat Shipman -- Uneasy alliance: the intersection of government science, politics and policymaking / Ruth J. Katz -- On the relationship between scientists and journalists: reflections by an ethicist / Robert J. Levine -- Don't shoot the messenger / Laura Spinney -- Future trends in medical research publishing / Harry W. McConnell, Ashley Pardy -- Conclusion: the ethics of scientific disclosure / Peter J. Snyder, Linda C. Mayes.
Includes bibliographical references (pages 213-238) and index.
Print version record.
Elsevier
Keywords: Communication in science; Science -- Social aspects; Communication in science; Science -- Social aspects; Science; Communication; Disclosure; Electronic books